Análise da eficiência energética em indústrias madeireiras através da lógica fuzzy - Caneppele, Fernando de Lima; Seraphim, Odivaldo José [UNESP] (EIA Energy in Agriculture, 2013)
This paper presents the application of fuzzy theory to support the decision of implementing energy efficiency program in sawmills operating in the processing of Pinustaeda and Pinuselliotii. The justification of using a system based on fuzzy theory for analysis of consumption and the specific factors involved, such is the diversity of rates / factors. With the fuzzy theory, we can build a reliable system for verifying actual energy efficiency. The indices and factors characteristic of industrial activity were measured and used as the basis for the fuzzy system. We developed a management system and technology. The system involves the management practices in energy efficiency, maintenance of plant and equipment and the presence of qualified staff. The technological system involves the power factor, load factor, the factor of demand and the specific consumption. The first response provides the possibility of increased energy efficiency and the second level of energy efficiency in the industry studied. With this tool, programs can be developed for energy conservation and energy efficiency in the industrial timber with wide application in this area that is as diverse as production processes. The same systems developed can be used in other industrial activities, provided they are used indices and characteristic features of the sectors involved.

Este trabalho apresenta a aplicação da teoria fuzzy como suporte a decisão da implantação de programa de eficiência energética em serrarias que atuam no processamento de Pinus elliotti e Pinus taeda. A justificativa do uso de um sistema baseado na teoria fuzzy para análise dos consumos específicos e dos fatores envolvidos, está na diversidade de tais índices/fatores. Com a teoria fuzzy, pode-se construir um sistema confiável para a verificação real da eficiência energética. Os índices e fatores característicos desta atividade industrial foram aferidos e são utilizados como base para o sistema fuzzy. Foi desenvolvido um sistema gerencial e um tecnológico. O sistema gerencial envolve as práticas de eficiência energética, a manutenção de instalações e equipamentos e a presença de corpo técnico qualificado. O sistema tecnológico envolve o fator de potência, o fator de carga, o fator de demanda e o consumo específico. O primeiro apresenta como resposta a possibilidade do aumento de eficiência energética e o segundo o nível de eficiência energética da indústria estudada. Com esta ferramenta, podem ser desenvolvidos programas de conservação de energia e de eficiência energética na área industrial madeireira com aplicação ampla nesta área que é tão diversificada quanto aos processos produtivos. Os mesmos sistemas desenvolvidos podem ser utilizados em outras atividades industriais, desde que sejam utilizados os índices e fatores característicos dos setores envolvidos.
Analysis of energy efficiency in woodindustry by fuzzy logic
Keywords: Wood industry; Energy efficiency; Fuzzy logic; Indústria da madeira; Eficiência energética; Lógica fuzzy